Pattern lock and the app based on context, ease of use aspect in comparison - Farid Fajriana Pulungan; Dodi Wisaksono Sudiharto; Tri Brotoharsono (IAES Indonesian Section, 2019)
Smartphone has been a popular device utilized to support productivity in human life and has become an integral part of human activities such as for communication, entertainment and social interaction. Those activities can be related to the information which needs to be protected because of its high privacy. Therefore, the smartphone needs a procedure that demonstrates an ability to secure that user information. However, more protective the scheme, more difficult the usage. Based on that pattern behavior, a good security scheme which support the users for easy security feature is urgently needed. One of such kind security features is authentication feature. In that manner, the ease of use aspect for acquiring the system by using an easy authentication mechanism becomes critically important. The ease of use intended is the efficiency of interaction between the user and that security feature for doing authentication including the time needed for doing that. This study developed the app which utilizes the context data, namely Geofilock. The context data meant is the location data based on the GPS and MAC address of the Wi-Fi. The system detected both context data and determined whether the smartphone needs to show the pattern screen lock as authentication feature or not, based on the context data analysis. The functionality of Geofilock works properly as shown by less user interaction number and less time needed by the user for obtaining the access. In addition, the app is easy to operate, as suggested by the user feedback.